2008
DOI: 10.1007/s10562-008-9769-x
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Production from Aqueous Solutions of Alcohol as Model Compounds of Biomass Using Visible Light-Responsive TiO2 Thin Films

Abstract: Visible light-responsive TiO 2 (Vis-TiO 2 ) thin films were prepared by a radio frequency magnetron sputtering deposition method. The photoelectrochemical performance was improved by adding various kinds and concentrations of alcohol, i.e., model compounds of biomass, to water. The separate evolution of pure H 2 was observed to proceed efficiently on these Vis-TiO 2 thin films under visible light irradiation by using an aqueous solution of methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Furthermore, it was found that the anodic photocurrent decreases when the film thickness of UV-TiO 2 exceeds 100 nm, suggesting that the thick UV-TiO 2 layer (about 150 nm) acts as a barrier layer to prevent efficient electron transfers from Vis-TiO 2 to the Ti metal substrate, thus increasing the charge recombination rate of the photoformed electrons and holes [21,22]. It can be considered that the contact between anatase (UV-TiO 2 ) and rutile (Vis-TiO 2 ) phases is not the major factor to facilitate the charge separation because the conduction band of UV-TiO 2 is higher than Vis-TiO 2 , i.e., anatase-rutile contact can bring negative effect for charge separation [23]. The main origins of the visible light activity of DL-TiO 2 (X)/Ti electrodes can be ascribed to Vis-TiO 2 outer layer, since the O/Ti ratio of the Vis-TiO 2 thin film gradually decreases from the top surface (O/Ti ratio of 2.00) to the inside bulk (O/Ti ratio of 1.93).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was found that the anodic photocurrent decreases when the film thickness of UV-TiO 2 exceeds 100 nm, suggesting that the thick UV-TiO 2 layer (about 150 nm) acts as a barrier layer to prevent efficient electron transfers from Vis-TiO 2 to the Ti metal substrate, thus increasing the charge recombination rate of the photoformed electrons and holes [21,22]. It can be considered that the contact between anatase (UV-TiO 2 ) and rutile (Vis-TiO 2 ) phases is not the major factor to facilitate the charge separation because the conduction band of UV-TiO 2 is higher than Vis-TiO 2 , i.e., anatase-rutile contact can bring negative effect for charge separation [23]. The main origins of the visible light activity of DL-TiO 2 (X)/Ti electrodes can be ascribed to Vis-TiO 2 outer layer, since the O/Ti ratio of the Vis-TiO 2 thin film gradually decreases from the top surface (O/Ti ratio of 2.00) to the inside bulk (O/Ti ratio of 1.93).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between the surface electronic structure measured using the conventional PYSA and the photocatalytic activity have been reported by Yamagishi et al, 7 Song et al, 8 Miyamura et al, 9 and Fukumoto et al 10 On the other hand, the high wettability of the TiO2 surface has been extensively studied, [11][12][13][14][15][16][17] and has attracted considerable attention. Therefore, a newly designed PYSA was applied in order to evaluate the change in the TiO2 surface depending upon the humidity.…”
Section: Introductionmentioning
confidence: 88%
“…Similar results were reported for hydrogen production from aqueous C1-C4 alcohols over Pt/TiO 2 photocatalysts. [56][57][58][59] Thus, the dissociative adsorption of alcohol over Pt/TiO 2 shown in eqn (8.17) appears to mainly govern the reaction rate. Another possibility is that, with increasing carbon chain length and branches, the steric hindrance in the molecule reduces the hydrogen production rate.…”
Section: Reactivity Of Substratesmentioning
confidence: 99%